HOTEL INDUSTRY COMPETITIVENESS IN COVID 19 PANDEMIC ENVIRONMENT IN KENYA: HOW TECHNOLOGICALLY READY ARE THE HOTELS? - Nzisa, Jane; Gitahi, Njenga; Kiprop, Symon (My University, 2021)
Since December 2019, the COVID-19 pandemic has had a devastating impact on te totel industry leading to deep losses among industry players and forcing some to shut down altogether. For those that would survive the crisis, their competitiveness could be at risk unless they demonstrate strategic readiness. The competitiveness found in modern organizations is, however, increasingly determined by the strategic readiness or capability of it assets, notably technology. However, the strategic readiness of the hotel industry needed to be established. Therefore, this paper explores the strategic teachnology readiness of the star-rated hotels in Kenya for competitiveness in the Covid 19 pandemic environment. The paper is guided by the Chamberlain's theory of strategy. A descriptive cross sectional survey design targeting 138 star-rated hotels in the country selected through systematic random sampling. Data was collected using questionnaires and interview schedules. Qualitative data was analyzed using content anaysis with the aid of Nvivo software while quantitative data was analyzed using both ddescriptive and inferential statistical analysis with the aid of SPSS version 24.0. Specifically, the study used the bivariate regression model to assess the relationship between the variables. The study found that technology readiness significantly influenced the competitiveness of star-rated hotels in the Covid 19 pandemic environment in Kenya. There is need for the hotels to adopt a more proacticve approach in setting their technological systems for any
Keywords: strategic readiness; technology; ompetitiveness; pandemic environment; star-rated hotels; Covid 19